Geopolitical Analysis of the Crimean Peninsula and the Black Sea in the Context of Turkish-Russian Energy Policy - F. Gide (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
The introductory paragraphs of the article consider the historical approach to how important the black sea and Crimea are in geopolitical terms, which became more important after the eighteenth century. In addition, the main issue that was studied in the article; the Maritime geopolitics of the black sea and Crimean peninsulas in accordance with the new situation that arose as a result of the annexation of Crimea to Russia after the referendum, as well as the state of Turkey’s energy needs and how the issue of energy security will be resolved in the future. Although Turkey has two important waterways, such as the Straits of Istanbul and the Dardanelles, it has been appreciated why it cannot turn this superiority into some kind of advantage. The data used in the article is usually based on official reports published by government agencies. The point from which mutual trade relations between Turkey and Russia originate, through gas pipelines, and the benefits and harms of the situation are discussed. Both in the Black sea and partly in the Eastern Mediterranean, gas exploration operations are underway; their reflection in Turkish foreign policy has been deconstructed. Questions such as how much natural gas Turkey needs per year and which countries import gas that needs it were discussed with the data.